Towards Sustainable Inorganic Polymers: Production and Use of Alternative Activator - Lubica Kriskova; Efthymios Tatsis; Muhammad Afsar; David Delaere; Yiannis Pontikes (Materials Proceedings, 2022)
Inorganic polymers are considered to have a much smaller CO2 footprint than traditional Portland cements. The possible environmental impact reduction was calculated to be up to 77% of a CEMI ordinary Portland cement (OPC)-based mortar, while the CO2 emissions were reduced by up to 83%. The highest contribution to the total CO2 footprint of inorganic polymers is related to the manufacturing of alkali activators. Within this context, the current work discusses the synthesis of inorganic polymers made from Fe-rich precursor and alternative silicate solutions. The obtained results indicate that there is no significant difference between an inorganic polymer prepared from alternative and commercially available solutions, which confirms that the waste glass can be use as alternative raw material in the production of sodium silicate.